Estimates of peroxidase and polyphenol oxidase enzyme activities in different accessions of Pongamia pinnata L. - Shukla, Deepty; Kumar, R.V.; Pandey, S.K.; Ahlawat, S.P. (Indian Journal of Agroforestry, 2020)
.